Identification and characterisation of single nucleotide polymorphisms in cytochrome P450 2D6 gene in Malaysian breast cancer patients - Chin, Fee Wai (2012)
Worldwide as well as Malaysia, breast cancer remains the most common type of malignancy and also the major cause of cancer related deaths among women. Tamoxifen is extensively used as adjuvant hormonal therapy for estrogen receptor-positive breast cancer patients to reduce risk of recurrence and mortality. However, variability in response to tamoxifen is observed among breast cancer patients. This may be due to genetic polymorphisms of cytochrome P450, family 2, subfamily D, polypeptide 6 (CYP2D6) gene that influence the CYP2D6 enzyme activity in tamoxifen metabolism. To date, no study has been conducted to investigate single nucleotide polymorphism (SNP) profiles of CYP2D6 gene specific to Malaysian breast cancer patients. Hence, this study aimed to identify SNPs in the coding regions of the CYP2D6 gene in Malaysian breast cancer patients and also to predict the functional effects of the identified non-synonymous SNPs.The identification of SNPs was successfully achieved through utilisation of high resolution melting (HRM) analysis and confirmatory DNA sequencing. A total of 51 SNPs of the CYP2D6 gene consisting of 40 known SNPs and 11 novel SNPs were identified in this study. Complete genotype concordance was observed in both tumour DNA (carcinoma tissues) and germline DNA (adjacent normal tissues and blood) of 16 breast cancer patients for all the 51 SNPs. Results from logistic regression analysis showed that metastasis status, hormonal receptors status, ethnicity and SNP c.100C>T are the predictors that contribute significantly in predicting survival of breast cancer patients. Apart from that, nine out of 24 non-synonymous SNPs consisting of c.100C>T, c.271C>A, c.545T>C, c.800C>G, c.1316G>A, c.1318C>T, c.1322G>A, c.1405C>G and c.1444G>A are predicted to be deleterious SNPs by in silico analysis using bioinformatics software. CYP2D6*10/*10 was found to be the most prevalent genotype in both Malay and Chinese breast cancer patients with genotype frequency of 28.9% and 57.1%, respectively. On the contrary, Indian breast cancer patients had a high prevalence of CYP2D6*4/*10 genotype with genotype frequency of 42.8%. It has been suggested by previous studies that CYP2D6 phenotypes determined based on CYP2D6 genotypes can be used for predicting the efficacy of tamoxifen. In relation to CYP2D6 phenotype, 61.5% of Malay patients were shown to have genotypes that categorised them as extensive metabolisers, hence, it is expected that the majority of them would benefit from tamoxifen therapy. On the contrary, 57.1% of Chinese as well as Indian patients were categorised as intermediate metabolisers, which suggest that they might experience reduced efficacy of tamoxifen therapy due to the reduction of CYP2D6 enzyme activity towards tamoxifen metabolism. This indicates that future clinical CYP2D6 genotyping may need to be considered prior to the selection of hormonal therapy for breast cancer patients. In conclusion, this study represents the first effort to identify CYP2D6 SNP profiles specific to Malaysian breast cancer patients. Additionally, this study also provides information on metaboliser status of the patients, which may potentially aid clinicians towards better treatment management of breast cancer in the future.